The Experiences of Migrants Trafficked from Bangladesh - Joarder, Munim; Miller, P. (SAGE, 2014)
This article examines a variety of experiences that trafficked illegal migrants, who had returned to Bangladesh after working in another country, encounter. Using survey research, we document considerable variation across countries of destination in the cost of migration, the amount of bribes paid to facilitators, and the reasons for returning home. Such variation was related to migrants’ assets, age, gender, and education, as well as the nature of the migration contract. A majority of therespondents discovered that their travel documents were fraudulent; three-quarters reported a variety of adverse working conditions in the destination country; and almost all the female migrants had experienced sexual harassment or assault. We believe that carefully conducted survey research such as ours can provide insights into the mechanisms of human trafficking, the risks involved in migration, and reasons that migrants are willing to take such risks.